Mental health in individuals with self-reported psychiatric symptoms during the COVID-19 pandemic: Baseline data from a swedish longitudinal cohort study - Rozental, Alexander; Sörman, Karolina; Ojala, Olivia; Jangard, Simon; El Alaoui, Samir; Månsson, Kristoffer N. T.; Shahnavaz, Shervin; Lundin, Johan; Forsström, David; Hedman-Lagerlöf, Maria; Lundgren, Tobias; Jayaram-Lindström, Nitya (Frontiers in Psychiatry, 2022)
Objective: Individuals with psychiatric disorders may be vulnerable and sensitive to rapid societal changes that have occurred during the COVID-19 pandemic. To fully understand the impacts, repeated measurements are warranted. However, to date, a large proportion of studies related to the pandemic are cross-sectional, low resolution (e.g., questionnaires with few items) and majority of the investigations target healthy populations. In order to address the limitations in the literature, the current longitudinal study set out to perform monthly assessment of individuals with common psychiatric disorders using established and self-reported questionnaires. Methods: Recruitment of individuals was running between July 2020 and June 2021 using an online survey. The patients answered questions on demographics, psychiatric history, current psychiatric symptoms, somatic health, health-care contacts and any changes therein during the pandemic. Monthly, longitudinal assessments are still ongoing (consenting participants provide data for 1 year), and here we present descriptive statistics from the initial baseline measurement. Results: A total of 6.096 participants (average age 35 years) submitted complete baseline data. Marital status and number of years of education were evenly distributed in this population. The most common lifetime psychiatric disorder was depressive disorder (80.5%) and generalized anxiety disorder (45.9%), with a substantial proportion having severe symptoms of depression (30.5%) and anxiety (37.1%). Lifetime suicidal ideation (75.0%) and non-suicidal self-harm (57.7%) were prevalent in the group and 14.5% reported drug use during the pandemic. Allergies (36.8%) were the most common somatic condition, followed by irritable bowel syndrome (18.7%). For those having experienced a traumatic event, 39% showed symptoms indicating PTSD. Regarding contact with mental health services during the pandemic, 22% had established a new contact, and 20% reported having increased their psychiatric medication compared to before. Conclusions: Baseline data collected during the pandemic with pre-existing psychiatric disorders demonstrate that this sample represents a population suitable for an investigation on the long-term impact of the pandemic. Follow-up questionnaires over a 12-month period are being collected and will indicate how the health and well-being of this population develops during the changes and uncertainties that have been characteristic of the past 2 years.